Dimensions quotients - Passi, I.B.S. (Indian math. Soc., 2009)
We present two approaches , one homological and the other simplicial for the investigation of dimension quotient of groups.The theory is illistrated , in a particular , with a conceptual discussion of fourth and fifth dimension quotient.
Only IISERM authors are available in the record.
Keywords: Mathematics